القيمة الاقتصادية المضافة بين مؤيديها ومعارضيها (دراسة تطبيقية لأحد المفاهيم الأكثر جدلاً لتقييم الأداء) - العلي, سوزان (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هذه الورقة تهدف إلى التعريف بمقياس القيمة الاقتصادية المضافة (Economic Value Added / EVA)،الذي مثل صيحةً ضمن مقاييس الأداء، كإجراء جديد لقياس أداء المنظمات الداخلي من خلال قدرتها على خلق القيمة، وكبديل للمؤشرات المستخدمة تقليدياً والقائمة على قياس ربحية هذه المنظمات.تناولت الورقة نشأة هذا المفهوم، وأسباب ظهوره، وتعريفه من الناحية النظرية والمحاسبية، إضافة إلى النقاط الإيجابية والسلبية الناجمة عن استعماله، من خلال مراجعة أهم الدراسات التي تناولت التجارب العملية لهذا المقياس، كما تم تطبيق هذا المقياس على الشركات المدرجة في سوق مصر للأوراق المالية، لدراسة العلاقة بين هذا المقياس وبين أسعار الأسهم خلال الفترة الممتدة بين 2011 و2014،وبيان مدى قدرته على تفسير التغيرات في أسعار أسهم هذه الشركات.توصلت الدراسة إلى عدم وجود علاقة ذات دلالة إحصائية بين أسعار أسهم هذه الشركات وبين القيمة الاقتصادية المضافة لها، وبالتالي عدم فعالية هذا المؤشر عند استخدامه كأداة لتقييم أداء هذه الشركات وتحفيز المدراء.This paper reinvestigate the Economic Value Added(EVA), as a performance measure of the organization's ability to create value. This measure is suggested to be used as an alternative to the traditionally indicators based on the profitability of these organizations.The paper introduce the concept of EVA, the reasons of its appearance from both theoretically and accounting view, the positive and negative points resulting from the use of it by reviewing the most important studies on practical experiences of this measure.The application of this measure has been done on the companies which is listed in the Egypt Stock Exchange, to study the relationship between this measure and share price, and the extent of its ability to interpret the changes in the prices of shares of these companies during the period 2011-2014.The study concluded that there are no statistically significant differences between the stock prices of these companies and the economic value added, and therefore the ineffectiveness of this measure as atool to evaluate the performance of these companies and motivate managers.